The physics of cutmarks - Potter, Sheridan L., author; Todd, Larry C., author (Colorado State University. Libraries, 2004)
Cutmarks are the most direct evidence of faunal butchery by humans ; however, understanding the physical properties associated with their creation is critical when interpreting the archaeological record. By quantifying the minimum amount of force required to cut through soft tissue and the minimum amount of force required to produce a visible cutmark on the surface of bone, and then correlating those values with the maximum amount of force exerted by a human butchering with a stone tool, archaeologists will better understand the conditions conducive to creating cutmarks. A porcine metatarsal served as the specimen for the cutting experiment, while obsidian and chert flakes, and a scalpel blade were used as the cutting tools. Axial cutting force was measured with a dynamic loading cell, accurate to the nearest Newton. Cutmarks were replicated with rubber latex and were analyzed using a scanning electron microscope at varying degrees of magnification, and depth was measured to the nearest micrometer. Twenty adults (10 male and 10 female) volunteered to perform an experiment measuring the maximum amount of force that could be exerted in a kneeling position while holding a small flake and a large biface. Force was measured using a digital scale accurate to the nearest tenth of a kilogram. Results have shown that less force is required to cut through soft tissue using obsidian as opposed to chert flakes, the amount of force required to produce a visible cutmark on a bone is constant, and that on average males can exert a greater maximum force using both large and small stone tools than females.
Keywords: Stone implements -- Analysis; Animal remains (Archaeology) -- Analysis; Bones -- Analysis